Audit Committees in Central Banks - Sullivan, Kenneth (IMF Working Papers; Working Paper ;, 2007)
This paper reviews the tasks and design of audit committees, increasingly recommended as a way to strengthen financial accountability and good central bank governance. It outlines the motivations for the establishment of audit committees in commercial corporations and public sector entities, and explains how audit committees interact with other governance bodies within a central bank. The paper focuses on the functions of an audit committee, since the terminology of the governance structure is often country-specific. It summarizes operational issues to consider in designing an effective audit committee and discusses the implications for central bank legislation.